Trial-based functional analysis training for technical assistant - Guimarães, Ana Cristina Israel; Garcia, Rafael Vilas Boas (Perspectivas em Análise do Comportamento, 2025)
Autism Spectrum Disorder (ASD) is characterized by deficits in communication and fixed and repetitive behaviors. The literature points out that individuals with ASD are more likely to exhibit inappropriate behaviors. Experimental functional analysis is one method that provides the most reliable and precise data on identifying the function of behavior. Thus, the research aims to verify the effects of training for the implementation of Trial Based Functional Analysis (TBFA) on staff. A staff participated in this study in a quasi-experimental, single-subject, type A-B design. The results were analyzed based on the initial assessment, training exercises and, also, through videos from the baseline and post-training session. The results of the study were promising, indicating that the effect of the training package was efficient. This assessment is important because it is brief, provides accurate data about the function of behavior and because it is viable to apply in a natural context such as classrooms and ABA intervention clinics.